Design Rules for Tailoring Antireflection Properties of Hierarchical Optical Structures. Issue 13 (18th May 2017) - Leon, Juan J. Diaz; Hiszpanski, Anna M.; Bond, Tiziana C.; Kuntz, Joshua D.
Abstract : Hierarchical structures consisting of small sub‐wavelength features stacked atop larger structures have been demonstrated as an effective means of reducing the reflectance of surfaces. However, optical devices require different antireflective properties depending on the application, and general unifying guidelines on hierarchical structures' design to attain a desired antireflection spectral response are still lacking. The type of reflectivity (diffuse, specular, or total/hemispherical) and its angular‐ and spectral‐dependence are all dictated by the structural parameters. Through computational and experimental studies, guidelines have been devised to modify these various aspects of reflectivity across the solar spectrum by proper selection of the features of hierarchical structures. In this wavelength regime, micrometer‐scale substructures dictate the long‐wavelength spectral response and effectively reduce specular reflectance, whereas nanometer‐scale substructures dictate primarily the visible wavelength spectral response and reduce diffuse reflectance. Coupling structures having these two length scales into hierarchical arrays impressively reduces surfaces' hemispherical reflectance across a broad spectrum of wavelengths and angles. Such hierarchical structures in silicon are demonstrated having an average total reflectance across the solar spectrum of 1.1% (average weighted reflectance of 1% in the 280–2500 nm range of the AM 1.5 G spectrum) and specular reflectance <1% even at angles of incidence as high as 67°. Abstract : Broadband and pseudo‐omnidirectional antireflection is demonstrated with hierarchically structured silicon. Through computational and experimental studies, guidelines are devised to modify the type of reflectivity and its angular‐ and spectral‐dependence across the solar spectrum by proper selection of the micrometer‐ and nanometer‐scale features making up these hierarchical structures.